Splošni pregled avtoimunskih dermatoloških obolenj - Kren, Anja (Placebo, 2025)
Autoimmune skin diseases are caused by a misdirected immune response that attacks the body's own skin structures. They differ in the target of autoantibodies and pathogenesis, but are united by autoantibodies that trigger inflammation, blistering, depigmentation, or other skin changes. Diagnostic and therapeutic approaches depend on knowledge of the mechanism of disease development, which is still being discovered. For now, the treatment is based on immunosuppression, but the development of biological drugs offers new hope for targeted therapy.
Keywords: autoimmune skin disease; Avtoimunske bolezni; avtoimunske bolezni kože; dermatosis; dermatoza; luskavica; pemfigoid; pemfigus; pemphigoid; pemphigus; psoriasis